PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 4 LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - Syuhada, Yulia; Rahmi, Rahmi; Yunita, Alfi (STKIP PGRI Sumbar, 2013)
This research is based by the lack of understanding of the mathematical concepts that lead to low student math achievement of studentâs. This research is aimed at knowing wheather the understanding of the mathematics concept of the students who are treated by used implementating cooperative learning methodâs Student Teams Achievement Division (STAD) is better than understanding of the mathematics concepts of the students with conventional teaching class VIII SMPN 4 Lembah Melintang West Pasaman and to determine the effectiveness of application of the cooperative learning methodâsÂ Student Teams Achievement Division (STAD) in mathematics class VIII SMPN 4 Lembah Melintang West Pasaman. This type of research is experimental with random study design on the subject. The technique of data analysis used was the Mann-Whitney test with the help by MINITAB. Based on data analysis, it is known that both sample classes does not normal distribution and homogeneous distribution at Î± = 0,05. Hypothesis test result obtained probability value = 0,0199 is less thanÂ Î± = 0,05, so Â the hypothesis is accepted. Consequently, it can be concluded that the understanding of the mathematics concept of the students who are treated by used implementing cooperative learning methodâs Student Teams Achievement Division (STAD) is better than understanding of the mathematics concept of the students with conventional teaching class VIII SMPN 4 Lembah Melintang Kabupaten West Pasaman.